Religious Minorities in Ukraine Amidst Russia's Invasion: Security, Legal, and Institutional Challenges (Stato, Chiese e pluralismo confessionale, 2025)
Russia’s full-scale invasion has posed significant challenges to religious freedom in Ukraine. Nearly 700 religious sites have been destroyed by ongoing Russian airstrikes and shelling targeting civilians across Ukraine. At the same time, Russia continues to suppress religious minorities and terrorize civilians in occupied Ukrainian regions, subjecting believers to persecution, arrests, tortures, and executions. The occupation authorities enforce Russification and the Russian World ideology, promoting the Russian Orthodox Church while suppressing other faiths. The Kremlin has weaponized religion as an instrument of ideological control, transforming Russian religious centers into mouthpieces of propaganda and channels of influence. In response, Ukraine has sought to limit Russian interference in religious affairs, leading to legislative initiatives that have sparked international debate. The country faces challenges in balancing national security with religious freedom, concerning the influence of Russian religious centers and policies on military conscription. The lack of clear provisions for conscientious objection has resulted in the legal persecution of believers from minority faiths. Additionally, mass migration and conscription disrupted religious communities, causing colossal displacement and leadership crises. This paper examines the intersection of war, religious policy, and human rights, analyzing how Ukraine navigates threats to its sovereignty while upholding its commitment to religious freedom.